Phytochemical constituents, chemotaxonomic significance and anti-arthritic effect of Eucommia ulmoides Oliver staminate flowers - Rui Li; Lanlan Nie; Qing Wang; Danwei Ouyang; Lei Zhang; Ying Yuan; Yanlong Hong; Jianying Wang; Xiao Hu (Natural Product Research, 2020)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Study on Durability against Dry-Wet Cycles and Chloride Ion Erosion of Concrete Revetment Materials at the Water-Level-Fluctuations Zone in Yellow River Delta Wetlands - Rui Sun; Dongmin Wang; Yiren Wang; Lei Zhang; Yue Gu (Wetlands, 2020)

Busulfan Suppresses Autophagy in Mouse Spermatogonial Progenitor Cells via mTOR of AKT and p53 Signaling Pathways - Rui Wei; Xiaoyu Zhang; Yihui Cai; Hongyang Liu; Bingyuan Wang; Xiaodong Zhao; Kang Zou (Stem Cell Reviews and Reports, 2020)

α-Synuclein aggregation and transmission in Parkinson’s disease: a link to mitochondria and lysosome - Rui Wang; Hongyang Sun; Haigang Ren; Guanghui Wang (Science China Life Sciences, 2020)

A Comprehensive Experimental Study on Mechanical Behavior, Microstructure and Transport Properties of 3D-printed Rock Analogs - Rui Song; Yao Wang; Sergey Ishutov; Gonzalo Zambrano-Narvaez; Kevin J. Hodder; Rick J. Chalaturnyk; Shuyu Sun; Jianjun Liu; Ranjith P. Gamage (Rock Mechanics and Rock Engineering, 2020)

Porphyry mineralization in the Tethyan orogen - Rui Wang; Dicheng Zhu; Qing Wang; Zengqian Hou; Zhiming Yang; Zhidan Zhao; Xuanxue Mo (Science China Earth Sciences, 2020)

Duloxetine-Induced Neural Cell Death and Promoted Neurite Outgrowth in N2a Cells - Wanli Gao; Rui Chen; Nan Xie; Daolin Tang; Borong Zhou; Ding Wang (Neurotoxicity Research, 2020)
Duloxetine is a clinical drug that is primarily used for treatment of depression and pain, but it has side effects of addiction and tolerance. Cytochrome P450 (CYP) is its metabolic enzyme, and the drug’s biofunction results from its neuro-protective effect in animal and cell models. We aimed to investigate the duloxetine-induced neural cytotoxicity effect and its performance in an N2a cell neurite outgrowth model. Cell death was assessed as cell viability using a Cell Count Kit-8 and further evaluated using bright-field images, propidium iodide (PI) and annexin V staining, colony-formation analysis, TUNEL staining of the cells, and biochemical testing. N2a cells were committed to differentiation by serum withdrawal and RA induction, and the neurite outgrowth was evaluated as the number of differentiated cells, longest neurite length, and average neurite length. Cell cycle analysis, PI and annexin V staining, mRNA expression, and biochemical testing were used to evaluate the drug effects on differentiation. The induction of neural cell death by duloxetine was not affected by classic cell death inhibitors but was promoted by the CYP inducer rifampicin. N2a cell neurite outgrowth was promoted by duloxetine via reduction of the CYP2D6 and MDA levels and induction of Bdnf protein levels. Duloxetine induces neural cell death through effects on CYP and promotes N2a cell neurite outgrowth by regulating CYP, Bdnf protein, and the intracellular lipid peroxidation level.

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Application of Ultrasonic-Rebound Method in Fast Prediction of Rock Strength - Rui Wang; Xianghui Deng; Yaoyao Meng; Daohong Xia (Geotechnical and Geological Engineering, 2020)

Reducible Fraction Dominates the Mobility of Vanadium in Soil Around an Iron Smelter - Long Zhijie; Huang Yi; Zhang Wei; Shi Zhangliang; Yu Daming; Chen Yin; Liu Chao; Wang Rui (Bulletin of Environmental Contamination and Toxicology, 2020)

Stability assessment of tunnel slopes along the Dujiangyan City to Siguniang Mountain Railway, China - Junpeng Huang; Chunwei Sun; Xiyong Wu; Sixiang Ling; Sen Wang; Rui Deng (Bulletin of Engineering Geology and the Environment, 2020)

Structural variability and niche differentiation of the rhizosphere and endosphere fungal microbiome of Casuarina equisetifolia at different ages - Rui Huang; Pan Chen; Xuan Wang; Huimin Li; Linzhi Zuo; Yaqian Zhang; Lei Li (Brazilian Journal of Microbiology, 2020)

Alginate oligosaccharide protects endothelial cells against oxidative stress injury via integrin-α/FAK/PI3K signaling - Jing Zhao; Yue Han; Zongqiu Wang; Rui Zhang; Guimei Wang; Yongjun Mao (Biotechnology Letters, 2020)

Atrophy of right inferior frontal orbital gyrus and frontoparietal functional connectivity abnormality in depressed suicide attempters - Yuyin Yang; Mohammad Ridwan Chattun; Rui Yan; Ke Zhao; Yu Chen; Rongxin Zhu; Jiabo Shi; Xinyi Wang; Qing Lu; Zhijian Yao (Brain Imaging and Behavior, 2020)

Fundamental Characteristics of Tropical Rain Cell Structures as Measured by TRMM PR - Yunfei Fu; Yilun Chen; Xiangdong Zhang; Yu Wang; Rui Li; Qi Liu; Lei Zhong; Qiong Zhang; Aoqi Zhang (Journal of Meteorological Research, 2020)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

Spatiotemporal variations in monthly relative humidity in China based on observations and CMIP5 models - Zigeng Niu; Lunche Wang; Lulu Fang; Jiarui Li; Rui Yao (International Journal of Climatology, 2020)
The variation trends in surface relative humidity (RH) are analyzed from 1961 to 2015 in China and its eight subregions based on monthly mean surface RH data from 2,474 stations provided by the National Meteorological Information Center of China (NMIC). The annual mean surface RH is 59% in China, with a clear maximum and minimum in South China (SC, 80%) and over the Tibetan Plateau (TP, 45%). From 1961 to 2002, the regional RH shows increasing trends in most regions of China, but a particularly sharp reduction in RH is evident since 2003 in each subregion and throughout China, leading to a decreasing RH in China from 1961 to 2015. The decline is larger in East China (EC, −0.58% decade −1 ) and SC (−0.59% decade −1 ) than that in the West of Northwest China (WNC, −0.11% decade −1 ) and North China (NC, −0.05% decade −1 ), and the decreasing trend is −0.30% decade −1 throughout all of China. A drier trend has been observed in most regions of China, especially in urban and high‐altitude areas, which suggests that the water vapour supply from the ocean is limited, accompanied by weakened monsoons, and the increase in sunshine duration in northwestern China also causes a decrease in surface RH. On the other hand, urbanisation will also lead to local urban dry island effects in some regions with large populations and rapid urbanization. Finally, the RH would decrease more rapidly under the RCP8.5 scenario than under the RCP4.5 scenario because of the asymmetrical increase in vapour pressure and saturation vapour pressure under increasing temperature.

Long‐term active restoration of extremely degraded alpine grassland accelerated turnover and increased stability of soil carbon - Yanfu Bai; Lina Ma; Abraham A. Degen; Muhammad K. Rafiq; Yakov Kuzyakov; Jingxue Zhao; Rui Zhang; Tao Zhang; Wenyin Wang; Xiaogang Li; Ruijun Long; Zhanhuan Shang (Global Change Biology, 2020)
Soil nutrient contents and organic carbon (C) stability are key indicators for restoration of degraded grassland. However, the effects of long‐term active restoration of extremely degraded grassland on soil parameters have been equivocal. The aims of this study were to evaluate the impact of active restoration of degraded alpine grassland on: (a) soil organic matter (SOM) mineralization; and (b) the importance of biotic factors for temperature sensitivity ( Q 10 ) of SOM mineralization. Soils were sampled from intact, degraded and restored alpine grasslands at altitudes ranging between 3,900 and 4,200 m on the Tibetan Plateau. The samples were incubated at 5, 15 and 25°C, and Q 10 values of SOM mineralization were determined. Structural equation modeling was used to evaluate the importance of vegetation, soil physico‐chemical properties and microbial parameters for Q 10 regulation. The Q 10 of N mineralization was similar among intact, degraded and restored soils (0.84–1.24) and was higher in topsoil (1.09) than in subsoil (0.92). The best predictive factor of CO 2 ‐ Q 10 for intact grassland was microbial biomass, for degraded grassland was basal microbial respiration, and for restored grassland was soil bulk density. Restoration by planting vegetation decreased the Q 10 of SOM mineralization as soil bulk density, the most important negative predictor, increased in restored grassland. The Q 10 of SOM mineralization in topsoil was 14% higher than in subsoil because of higher microbial abundance and exo‐enzyme activities. The NH 4 + content was greatest in intact soil, while NO 3 − content was greatest in degraded soil. The SOM mineralization rate decreased with grassland degradation and increased after long‐term (>10 years) restoration. In conclusion, extremely degraded grassland needs proper long‐term management in active restoration projects, especially for improvement of soil nutrients in a harsh environment.

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Research on the Bearing Capacity of a Damaged Jacket Repaired by a Grouting Clamp Based on a Type of Wedge Gripping - Bo Zhang; Qing Rui Zhang; Tao Wang; Zhuo Wang (Journal of Marine Science and Engineering, 2020)
In the process of repairing a damaged jacket with a grouting clamp, it is necessary to analyze the bearing capacity of the damaged structure to determine whether it meets requirements for maintenance and reinforcement. On the basis of previous research results, this paper proposes a design scheme of a grouting clamp based on wedge gripping, which can effectively improve the local bearing capacity of the jacket by more than 35%. The elastic–plastic theory was used to analyze the bearing capacities of steel pipe piles under three different conditions (ideal steel pipe, bending steel pipe and steel pipe with a defective section) and with reinforcement by a grouting hoop. The bearing capacity of the mechanical grouting clamp was analyzed, and the resulting theoretical design was verified by a bearing performance experiment. The results support the conclusion that the wedge mechanical grouting clamp can effectively strengthen local jacket members.

CD49a+CD49b+ NK cells induced by viral infection reflect an activated state of conventional NK cells - Wenhan Li; Jing Zhou; Xianwei Wang; Yuzhang Wu; Lilin Ye; Haiming Wei; Rui Sun; Zhigang Tian; Hui Peng (Science China Life Sciences, 2020)

Gas Reservoir Characterization Using Lp-Norm Constrained High-Resolution Seismic Spectral Attributes - Tieyi Wang; Sanyi Yuan; Rui Wang; Shan Yang; Shangxu Wang (Pure and Applied Geophysics, 2020)

Cytokinin (6-benzylaminopurine) elevates lignification and the expression of genes involved in lignin biosynthesis of carrot - Ahmed Khadr; Ya-Hui Wang; Rong-Rong Zhang; Xin-Rui Wang; Zhi-Sheng Xu; Ai-Sheng Xiong (Protoplasma, 2020)

Os4BGlu14, a monolignol β-Glucosidase, negatively affects seed longevity by influencing primary metabolism in rice - Rui-Juan Ren; Pei Wang; Li-Na Wang; Jing-Ping Su; Lin-Jing Sun; Yue Sun; De-Fu Chen; Xi-Wen Chen (Plant Molecular Biology, 2020)

Energy conservation and carbon reduction potential for solid waste in China - Minxi Wang; Zhi Li; Lu Chen; Ping Liu; Rui Zhang; Wei Liu; Yu Ma; Yajie Wang; Xin Li (Environmental Science and Pollution Research, 2020)

Research on multiple effects of fixed-asset investment on energy consumption——by three strata of industry in China - Rui Wang; Zhongying Qi; Yumin Shu (Environmental Science and Pollution Research, 2020)

Non-thermal plasma-enhanced low-temperature catalytic desulfurization of electrolytic aluminum flue gas by CuO-ZrSnO4: experimental and numerical analysis - Zhiyuan Ning; Lianshuang Jiang; Zeyue Wang; Rui Huang; Zhenyu Zhang; Qiulin Zhang; Ping Ning (Environmental Science and Pollution Research, 2020)

Genome-wide identification of microRNAs and phased siRNAs in soybean roots under long-term salt stress - Qian Wang; Yingxia Yang; Guoqing Lu; Xianjun Sun; Youren Feng; Shuangyong Yan; Huiyuan Zhang; Qiyan Jiang; Hui Zhang; Zheng Hu; Rui Chen (Genes & Genomics, 2020)

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Multi-AUVs Cooperative Target Search Based on Autonomous Cooperative Search Learning Algorithm - Yuan Liu; Min Wang; Zhou Su; Jun Luo; Shaorong Xie; Yan Peng; Huayan Pu; Jiajia Xie; Rui Zhou (Journal of Marine Science and Engineering, 2020)
As a new type of marine unmanned intelligent equipment, autonomous underwater vehicle (AUV) has been widely used in the field of ocean observation, maritime rescue, mine countermeasures, intelligence reconnaissance, etc. Especially in the underwater search mission, the technical advantages of AUV are particularly obvious. However, limited operational capability and sophisticated mission environments are also difficulties faced by AUV. To make better use of AUV in the search mission, we establish the DMACSS (distributed multi-AUVs collaborative search system) and propose the ACSLA (autonomous collaborative search learning algorithm) integrated into the DMACSS. Compared with the previous system, DMACSS adopts a distributed control structure to improve the system robustness and combines an information fusion mechanism and a time stamp mechanism, making each AUV in the system able to exchange and fuse information during the mission. ACSLA is an adaptive learning algorithm trained by the RL (Reinforcement learning) method with a tailored design of state information, reward function, and training framework, which can give the system optimal search path in real-time according to the environment. We test DMACSS and ACSLA in the simulation test. The test results demonstrate that the DMACSS runs stably, the search accuracy and efficiency of ACSLA outperform other search methods, thus better realizing the cooperation between AUVs, making the DMACSS find the target more accurately and faster.

New Value-Added Sugar and Brown Sugar Products from Sugarcane: A Commercial Approach - Liu Yang; Shi-Yan Shen; Zhi-Neng Wang; Ting Yang; Jia-Wen Guo; Rui-Yun Hu; Yan-Fang Li; David M. Burner; Xiong-Mei Ying (Sugar Tech, 2020)

An Iterative Focal Denoising Strategy for Passive Seismic Data - Bin Hu; Deli Wang; Rui Wang (Pure and Applied Geophysics, 2020)

High-efficiency somatic embryogenesis techniques for different hybrids of cut lilies - Rui Yan; Chunxia Wang; Jinxia Wang; Ruxia Nie; Hongmei Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Effects of Cr(VI)-reducing bacteria on the behaviour of Cr(VI) adsorption by goethite and haematite: speciation and distribution - Chunyong Wang; Rui Wu; Jianbo Guo; Yanshan Cui (Journal of Soils and Sediments, 2020)

Down-regulation of SETD6 protects podocyte against high glucose and palmitic acid-induced apoptosis, and mitochondrial dysfunction via activating Nrf2-Keap1 signaling pathway in diabetic nephropathy - Xiang Wang; Qiling Liu; Deqin Kong; Zi Long; YuFang Guo; Shuang Wang; Rui Liu; Chunxu Hai (Journal of Molecular Histology, 2020)

Ultrafiltration and microfiltration membrane performance, cleaning, and flux recovery for microalgal harvesting - Rui Liu; Lan Wang; Li Yang; Qingling Liu; Yunxiao Gao; Jing Ye; Jingrong Xiao; Qiang Hu; Xuezhi Zhang (Journal of Applied Phycology, 2020)

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Selenium Deficiency in Chickens Induces Intestinal Mucosal Injury by Affecting the Mucosa Morphology, SIgA Secretion, and GSH-Px Activity - Xianjing He; Yucai Lin; Shuai Lian; Dongbo Sun; Donghua Guo; Jianfa Wang; Rui Wu (Biological Trace Element Research, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

Complete genome sequence of a novel mycovirus isolated from the phytopathogenic fungus Corynespora cassiicola in China - Yanfen Wang; Hang Zhao; Caiying Xue; Chao Xu; Yuehua Geng; Rui Zang; Yuxia Guo; Haiyan Wu; Meng Zhang (Archives of Virology, 2020)

An evaluation of the core bacterial communities associated with hypersaline environments in the Qaidam Basin, China - Derui Zhu; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Yongzhen Li; Rong Wang (Archives of Microbiology, 2020)

Formation of nano- or near-nanoparticles via oxidation in the Dabaoshan concealed deposit, Guangdong Province - Rui Liu; Jianjin Cao; Yongkang Deng; Guoqiang Wang; Xiang Liu (Arabian Journal of Geosciences, 2020)

Fabrication of Nanosuspensions to Improve the Oral Bioavailability of Total Flavones from Hippophae rhamnoides L. and their Comparison with an Inclusion Complex - Rui Tian; Hui Wang; Yi Xiao; Pengyue Hu; Ruofei Du; Xiufeng Shi; Zhengtao Wang; Yan Xie (AAPS PharmSciTech, 2020)

BDNF improves axon transportation and rescues visual function in a rodent model of acute elevation of intraocular pressure - Rui Du; Xu Wang; Shigang He (Science China Life Sciences, 2020)

Electroacupuncture improves myocardial ischemia injury via activation of adenosine receptors - Yulan Ren; Zhihan Chen; Rui Wang; Yang Yu; Dehua Li; Yonggang He (Purinergic Signalling, 2020)
Electroacupuncture (EA) can improve myocardial ischemia (MI) injury; nevertheless, the mechanism is not entirely clear. And there were disagreements about whether the effect of EA at acupoint in disease-affected meridian is better than EA at acupoint in non-affected meridian and sham acupoint. Here, we showed that the effect of EA at Neiguan (PC6) is better than EA at Hegu (LI4) and sham acupoint in affecting RPP and ECG, increasing ATP and ADO production, decreasing AMP production, and upregulating the mRNA expression levels of A1AR, A2aAR, and A2bAR; knockdown of A1AR or A2bAR reversed the effect of EA at PC6 in alleviating MI injury; knockdown of A2aAR had no influence on the cardiac protection of EA at PC6; thus, the cardioprotective effect of EA at PC6 needs A1AR and A2bAR, instead of A2aAR; considering that the cardio protection of adenosine receptor needs activation of other adenosine receptors, one of the reasons may be that after silence of A1AR or A2bAR, EA at PC6 could not impact the expression levels of the other two adenosine receptors, and after silence of A2aAR, EA at PC6 could impact the expression levels of A1AR and A2bAR. These results suggested that EA at PC6 may be a potential and effective treatment for MI by activation of A1AR and A2bAR.

Metabolomics Study of Flavonoids and Anthocyanin-Related Gene Analysis in Kiwifruit (Actinidia chinensis) and Kiwiberry (Actinidia arguta) - Min Yu; Yuping Man; Rui Lei; Xuemei Lu; Yanchang Wang (Plant Molecular Biology Reporter, 2020)
This study investigated the flavonoid compounds in Actinidia chinensis and Actinidia arguta fruits. A total of 125 flavonoids, including 9 anthocyanins, 12 catechins, 17 flavanones, 48 flavones (including 14 flavone C-glycosides), 29 flavonols, 6 isoflavones, and 4 proanthocyanidins, were identified in “Hongyang” kiwifruit (red flesh), “Jintao” kiwifruit, “Mini Amethyst” kiwiberry (purple flesh), and “Kuilv” kiwiberry. Thirty-nine metabolites showed significantly different contents between “Hongyang” and “Jintao,” and 38 of them showed higher content in “Hongyang,” whereas 39 metabolites showed significantly different contents between “Mini Amethyst” and “Kuilv,” and 31 of them showed higher content in “Mini Amethyst.” This result indicates the superior nutritional value of the pigmented kiwi cultivars in terms of flavonoids. Multivariate statistical analysis indicates that the variation in flavonoid profiles contributes to the pigmentation phenotypes of “Hongyang” and “Mini Amethyst.” Further comparative transcriptomic analysis revealed that structural genes in the anthocyanin synthesis pathway ( AcF3H , AcF3′H , AcDFR , AcUFGT ) and transcription factors ( AcMYB10 , AcbHLH5 ) may be involved in the pigmentation of the red-fleshed A. chinensis , whereas AaF3H , AaF3GT , and AaMYB110 may play important roles in the pigmentation of the purple-fleshed A. arguta . This study provides broader insight into the variation in flavonoid profiles among kiwifruit/berry, evaluates the flavonoid nutrition of the four cultivars, and provides additional evidence for the correlation between the genes and metabolites involved in flavonoid synthesis.

The abscisic acid receptor gene VvPYL4 positively regulates grapevine resistance to Plasmopara viticola - Li Liu; Chang-Yuan Liu; Hui Wang; Shu-Yi Yu; Tian-Shu Guan; Yu-Fei Huang; Rui-Chun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Role of the C9ORF72 Gene in the Pathogenesis of Amyotrophic Lateral Sclerosis and Frontotemporal Dementia - Zongbing Hao; Rui Wang; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2020)

The study on loess liquefaction in China: a systematic review - Siyue He; Xiuling Wang; Haobo Fan; Hao Wang; Rui Ren; Chunxia Guo (Natural Hazards, 2020)

Three new species of Terriera (Rhytismatales, Ascomycota) from China - Shu-Rui Cai; Shi-Juan Wang; Tu Lv; Cheng-Lin Hou (Mycological Progress, 2020)

Apigetrin ameliorates streptozotocin-induced pancreatic β-cell damages via attenuating endoplasmic reticulum stress - Rui Zhang; Jie Shi; Tingting Wang; Xiaonan Qiu; Ruixia Liu; Yitian Li; Qing Gao; Ning Wang (In Vitro Cellular & Developmental Biology - Animal, 2020)

Bacterial and Archaeal Communities within an Ultraoligotrophic, High-altitude Lake in the Pre-Himalayas of the Qinghai-Tibet Plateau - Rong Wang; Rui Han; Qifu Long; Xiang Gao; Jiangwa Xing; Guoping Shen; Derui Zhu (Indian Journal of Microbiology, 2020)

Mapping spatio-temporal dynamics of main water parameters and understanding their relationships with driving factors using GF-1 images in a clear reservoir - Shuai Zeng; Yunmei Li; Heng Lyu; Jiafeng Xu; Xianzhang Dong; Rui Wang; Ziqian Yang; Jianchao Li (Environmental Science and Pollution Research, 2020)

Technical efficiency estimation of China’s environmental protection enterprises and its heterogeneity - Ren Wang; Rui Wang; Xiaobo He (Environmental Science and Pollution Research, 2020)

Alleviation of Cd phytotoxicity and enhancement of rape seedling growth by plant growth–promoting bacterium Enterobacter sp. Zm-123 - Meng Zhang; Zonghui Jin; Xu Zhang; Guoliang Wang; Rui Li; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Spatio-temporal characteristics of the relationship between carbon emissions and economic growth in China’s transportation industry - Li Wang; Jie Fan; Jiaoyue Wang; Yanfei Zhao; Zhen Li; Rui Guo (Environmental Science and Pollution Research, 2020)

Development of SNP markers for the bighead carp (Hypophthalmichthys nobilis) by using transcriptomic sequences - Rui An; Jianjun Fu; Bingjie Jiang; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Zaijie Dong (Conservation Genetics Resources, 2020)

Low-frequency swell noise suppression based on U-Net - Rui-qi Zhang; Peng Song; Bao-hua Liu; Xiao-bo Zhang; Jun Tan; Zhi-hui Zou; Chuang Xie; Shao-wen Wang (Applied Geophysics, 2020)

Reconstructing the 3D digital core with a fully convolutional neural network - Qiong Li; Zheng Chen; Jian-Jun He; Si-Yu Hao; Rui Wang; Hao-Tao Yang; Hua-Jun Sun (Applied Geophysics, 2020)

A new phenanthropyran and a new biphenanthrene from the rhizomes of Dioscorea septemloba and their antioxidant activities - Tao He; Yi Liu; Rui-Feng Xiong; Xiao-Yu Li; Shou-Feng Wang; Chun-Ru Cheng (Natural Product Research, 2020)

Ablation of olfactory bulb glutamatergic neurons induces depressive-like behaviors and sleep disturbances in mice - Mao-Yun Yuan; Ze-Ka Chen; Jian Ni; Tian-Xiao Wang; Shi-Yu Jiang; Hui Dong; Wei-Min Qu; Zhi-Li Huang; Rui-Xi Li (Psychopharmacology, 2020)

Prefrontal Nectin3 Reduction Mediates Adolescent Stress-Induced Deficits of Social Memory, Spatial Working Memory, and Dendritic Structure in Mice - Hong-Li Wang; Ji-Tao Li; Han Wang; Ya-Xin Sun; Rui Liu; Xiao-Dong Wang; Yun-Ai Su; Tian-Mei Si (Neuroscience Bulletin, 2020)
Chronic stress may disrupt the normal neurodevelopmental trajectory of the adolescent brain (especially the prefrontal cortex) and contribute to the pathophysiology of stress-related mental illnesses, but the underlying molecular mechanisms remain unclear. Here, we investigated how synaptic cell adhesion molecules (e.g., nectin3) are involved in the effects of adolescent chronic stress on mouse medial prefrontal cortex (mPFC). Male C57BL/6N mice were subjected to chronic social instability stress from postnatal days 29 to 77. One week later, the mice exposed to chronic stress exhibited impaired social recognition and spatial working memory, simplified dendritic structure, and reduced spine density in the mPFC. Membrane localization of nectin3 was also altered, and was significantly correlated with behavioral performance. Furthermore, knocking down mPFC nectin3 expression by adeno-associated virus in adolescent mice reproduced the stress-induced changes in behavior and mPFC morphology. These results support the hypothesis that nectin3 is a potential mediator of the effects of adolescent chronic stress on prefrontal structural and functional abnormalities.

Redescription of five tintinnine ciliates (Alveolata: Ciliophora: Oligotrichea) from coastal waters of Qingdao, China - Yang Bai; Rui Wang; Wen Song; Toshikazu Suzuki; Xiaozhong Hu (Marine Life Science & Technology, 2020)

Thallus sectioning as an efficient monospore release method in Pyropia yezoensis (Bangiales, Rhodophyta) - Nianci Chen; Lei Tang; Xiaowei Guan; Rui Chen; Min Cao; Yunxiang Mao; Dongmei Wang (Journal of Applied Phycology, 2020)
The red seaweed Pyropia yezoensis is a marine crop of important economic value and is widely cultivated in the coastal areas of northern China. The current seedling-raising system relies on the germination of conchospores, a process not fast enough to meet the increasing demand from farmers. In this study, we developed a monospore-dependent seedling method based on the asexual reproduction of the Pyropia thallus. The Pyropia thallus was physically sectioned into small pieces (microthalli) that were cultivated at 15 °C. The algal cells in the microthalli became morphologically condensed, underwent cell division, and then developed into monospores on the 5th day. The monospores were able to attach to the seeding rope in 24 h and germinated into healthy thalli. To optimize the efficiency of monospore release, we tested the effect of temperature and the size and original positions of the microthalli as well as the age of the mother thallus. Microthalli with a size of 30–50 cells from the middle and apex of 21-day-old thalli cultivated at 15 ° C yielded the optimum production of monospores. Theoretically, in this thallus-to-thallus seeding strategy, 0.1 g of thallus could produce at least 10 7 monospores, with the same number of offspring thallus seedlings. Taking all of these advantages together, including the high efficiency, short time, low cost and easy operation, this physical sectioning method could serve as a promising seed source especially for new cultivars with superior traits in Pyropia farming and rapid replenishment of seedlings when thalli undergo disastrous diseases.

Efficient removal of tylosin by nitrogen-doped mesoporous carbon nanospheres with tunable pore sizes - Xingru Hu; Junwen Qi; Rui Lu; Xiuyun Sun; Jinyou Shen; Weiqing Han; Lianjun Wang; Jiansheng Li (Environmental Science and Pollution Research, 2020)

The impact of prenatal exposure to PM2.5 on childhood asthma and wheezing: a meta-analysis of observational studies - Wu Yan; Xu Wang; Tianyu Dong; Mengqi Sun; Mingzhi Zhang; Kacey Fang; Yi Chen; Rui Chen; Zhiwei Sun; Yankai Xia (Environmental Science and Pollution Research, 2020)

Distribution and risk of mercury in the sediments of mangroves along South China Coast - Rui-Fei Ma; Hao Cheng; Aniefiok Inyang; Ming Wang; You-Shao Wang (Ecotoxicology, 2020)

Modeling the ecosystem response of the semi-closed Daya Bay to the thermal discharge from two nearby nuclear power plants - Rui Jiang; You-Shao Wang (Ecotoxicology, 2020)

Pseudomonas Saliphila sp. nov., a Bacterium Isolated from Oil-Well Production Water in Qinghai Oilfield of China - Xiao-Juan Zhang; Hong-Can Liu; Yu-Guang Zhou; Xiao-Lei Wu; Yong Nie; Qi-Rui Li; Mei-Zhu Wang; Liang Zhao; Man Cai; Ying-Qian Kang (Current Microbiology, 2020)

Transcriptional regulation of microRNA-126a by farnesoid X receptor in vitro and in vivo - Yi Yan; Shichao Wang; Rui Wang; Puxuan Jiang; Yaqing Chen; Liang Zhang; Chenjiao Hou; Lisheng Zhang (Biotechnology Letters, 2020)

Fluoride-Induced Alteration in the Diversity and Composition of Bacterial Microbiota in Mice Colon - Rong Fu; Ruiyan Niu; Rui Li; Baijuan Yue; Xuhua Zhang; Qiqi Cao; Jundong Wang; Zilong Sun (Biological Trace Element Research, 2020)

Different Responses of Vegetation to Frozen Ground Degradation in the Source Region of the Yellow River from 1980 to 2018 - Rui Wang; Zhibao Dong; Zhengchao Zhou (Chinese Geographical Science, 2020)

Genetic variants in Ras/Raf/MEK/ERK pathway are associated with gastric cancer risk in Chinese Han population - Xiaowei Wang; Xu Wu; Junyi Xin; Shuwei Li; Rui Zheng; Dan Guan; Weida Gong; Qinghong Zhao; Meilin Wang; Haiyan Chu; Mulong Du; Guoquan Tao; et al. (Archives of Toxicology, 2020)

Transcriptome Profile Analysis of Resistance Inoculated by Dryopteris crassirhizoma Dryocrassin ABBA in Potato Tubers - Wenzhong Wang; Rui Gao; Tong Zhang; Lingling Chen; Peng Feng; Zongbao Zhao; Changxu Zhang; Fanxiang Min; Shuai Yang; Qi Wei; Mei Guo; Ying Chang (American Journal of Potato Research, 2020)

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Spatial Variation in Thermal Stress Experienced by Barnacles on Rocky Shores: The Interplay Between Geographic Variation, Tidal Cycles and Microhabitat Temperatures - Hui-Yu Wang; Ling Ming Tsang; Fernando P. Lima; Rui Seabra; Monthon Ganmanee; Gray A. Williams; Benny K. K. Chan (Frontiers in Marine Science, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

The role of miRNA-155 in monocrotaline-induced pulmonary arterial hypertension through c-Fos/NLRP3/caspase-1 - Shou-Dong Chai; Zhen-Kun Li; Rui Liu; Tao Liu; Ming-Feng Dong; Pei-Zhe Tang; Jian-Tang Wang; Sheng-Jun Ma (Molecular & Cellular Toxicology, 2020)

Visible and near-infrared spectroscopy with chemometrics are able to predict soil physical and chemical properties - Jinbao Liu; Jiancang Xie; Jichang Han; Huanyuan Wang; Jianhong Sun; Rui Li; Shaoxuan Li (Journal of Soils and Sediments, 2020)

Activation of Protein Kinase Cδ Contributes to the Induction of Src/EGF Receptor/ERK Signaling in Ammonia-treated Astrocytes - Guizhi Jia; Rui Wang; Yi Yue; Hongliang Dai (Journal of Molecular Neuroscience, 2020)

miR-140-3p aggregates osteoporosis by targeting PTEN and activating PTEN/PI3K/AKT signaling pathway - Ruofeng Yin; Jiajia Jiang; Huimin Deng; Zhaobin Wang; Rui Gu; Fei Wang (Human Cell, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Response Patterns of Biomarkers as Tools to Identify Toxic Effects of Cadmium and Lead on Bufo gargarizans Embryo - Rui Zheng; Minyao Wu; Hongyuan Wang; Jufang Peng (Bulletin of Environmental Contamination and Toxicology, 2020)

Experimental and numerical study on the load and deformation mechanism of a flexible net barrier under debris flow impact - Rui Jiang; Wen-ping Fei; Hong-wei Zhou; Miao Huo; Jia-wen Zhou; Jia-mei Wang; Jia-jun Wu (Bulletin of Engineering Geology and the Environment, 2020)

Precise vehicle dynamic heading and pitch angle estimation using time-differenced measurements from a single GNSS antenna - Rui Sun; Qi Cheng; Junhui Wang (GPS Solutions, 2020)

The characteristic of the synonymous codon usage and phylogenetic analysis of hepatitis B virus - Xiaoming Qi; Chaojun Wei; Yonghong Li; Yu Wu; Hui Xu; Rui Guo; Yanjuan Jia; Zhenhao Li; Zhenhong Wei; Wanxia Wang; Jing Jia; Yuanting Li; et al. (Genes & Genomics, 2020)
Background Hepatitis B virus (HBV) infection is a crucial medical issue worldwide. The dependence of HBV replication on host cell machineries and their co-evolutionary interactions prompt the codon usage pattern of viral genes to translation selection and mutation pressure. Objective The evolutionary characteristics of HBV and the natural selection effects of the human genome on the codon usage characteristics were analyzed to provide a basis for medication development for HBV infection. Methods The codon usage pattern of sequences from different HBV genotypes of our isolates and reference HBV genome sequences downloaded from the National Center for Biotechnology Information (NCBI) database were analyzed by computing the relative synonymous codon usage (RSCU), nucleotide content, codon adaptation index (CAI) and the effective number of codons (ENC). Results The highest ENC values were observed in the C genotypes, followed by the B genotypes. The ENC values indicated a weak codon usage bias (CUB) in HBV genome. The number of codons differentially used between the three genotypes was markedly higher than that of similarly used codons. High CAI values indicated a good adaptability of HBV to its host. The ENC plot indicated the occurrence of mutational pressure in the three genotypes. The mean Ka/Ks ratios in the three genotypes were lower than 1, which indicated a negative selection pressure. The CAI and GC3% plot indicated the existence of CUB in the HBV genome. Conclusions Nucleotide composition, mutation bias, negative selection and mutational pressure are key factors influencing the CUB and phylogenetic diversity in HBV genotypes. The data provided here could be useful for developing drugs for HBV infection.

A Comparison Between Lab-Scale and Hot-Melt-Extruder-Based Anti-inflammatory Ointment Manufacturing - Rishi Thakkar; Eman A. Ashour; Ashay Shukla; Rui Wang; Walter G. Chambliss; Suresh Bandari; Narasimha Murthy; Michael A. Repka (AAPS PharmSciTech, 2020)

Drought characteristics and its impact on changes in surface vegetation from 1981 to 2015 in the Yangtze River Basin, China - Weixia Jiang; Lunche Wang; Lan Feng; Ming Zhang; Rui Yao (International Journal of Climatology, 2020)
Located in the subtropical monsoon climate area of China, the Yangtze River Basin (YRB) had been frequently affected by drought events recently. Based on standardized precipitation evapotranspiration Index (SPEI) and enhanced vegetation index (EVI), the characteristics of drought in the YRB and the influence of drought on vegetation in different seasons were investigated by maximum correlation ( R max ) between 1981 and 2015. The results showed that: (a) Droughts occurred frequently but had no obvious regularity in the YRB from 1981 to 2015. The drought intensity in autumn and winter were slightly higher than that in spring and summer. The autumn droughts in Sichuan Basin were the most serious, followed by the spring droughts in the middle and lower reaches of the YRB; (b) Annual SPEI series at 102 stations exhibited a downward trend and 72 stations exhibited an upward trend. There was no station showing a significant downward trend and two stations showing a significant upward trend. There was a drying trend in autumn and winter, and a wetting trend in spring and summer. The eastern area of the YRB shows a more arid trend in spring and autumn, as well as in the southwest in winter; (c) 90% of YRB showed a significant positive correlation ( p

Dryness/wetness pattern over the Three‐River Headwater Region: Variation characteristic, causes, and drought risks - Sisi Li; Zhijun Yao; Rui Wang; Zhaofei Liu (International Journal of Climatology, 2020)
The dryness/wetness patterns are a significant reference for stakeholders in developing reasonable strategies in regard to water resource management, prediction, prevention of extreme events, and management of agricultural activities; however, no attempts have been made to systematically quantify the dryness/wetness patterns and drought conditions over the Three‐River Headwater Region (TRHR) of China, where the ecosystem is highly sensitive to climate change. The spatio‐temporal characteristics of dryness/wetness for TRHR, as well as the reference evapotranspiration (ETr), precipitation (Pre), and drought risk, were all investigated for the period of 1961–2015. Using the methods of FAO‐56 Penman–Monteith (FAO‐56), standardized precipitation evapotranspiration index (SPEI), the Manner–Kendall (M–K) test, Pettitt test, factor contribution rate, and correlation analysis, the variation in the patterns of dryness/wetness, ETr, and Pre, and the causes behind dryness/wetness were discussed. Results indicated that the TRHR underwent a wetting tendency, which was characterized by decreasing ETr and increasing Pre based on the SPEI‐12M during 1961–2015. Moreover, 1971–1980 was the driest period, while 2001–2015 was the wettest period. A significant difference between seasons was detected in the dryness/wetness patterns during all study periods, as well as in extreme droughts. The TRHR underwent an overall wetting trend with 85% of the stations' SPEI‐3M showing increased variation during spring, in contrast with the north–south distribution pattern of the dryness/wetness with variation in the SPEI during summer. Moreover, it can be seen that droughts with higher longest drought duration (LDD) and total drought duration (TDD) were mostly located on the edge of the eastern and northern TRHR. The influencing factors demonstrate the vital roles of Pre and ETr in generating variation in the dryness/wetness patterns of the southern and northern parts of the TRHR, respectively. There is evidence indicating that Niño3.4, North Atlantic oscillation, and Arctic oscillation played more important roles in the variation of dryness/wetness patterns and Pre in TRHR.

Moderate parasitoidism on pollinators contributes to population oscillations and increases species diversity in the fig-fig wasp community - Lin Wang; Li-Yuan Yang; Feng Zhang; Rui-Wu Wang (Theoretical Ecology, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Inhibition of miR-574-5p suppresses cell growth and metastasis and enhances chemosensitivity by targeting RNA binding protein QKI in cervical cancer cells - Rui Tong; Jingru Zhang; Chunyan Wang; Qian Li; Ling Wang; Mingxiu Ju (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Antifungal Activity of Magnesium Oxide Nanoparticles: Effect on the Growth and Key Virulence Factors of Candida albicans - Fanzhi Kong; Jiaying Wang; Rui Han; Shuaiqi Ji; Jin Yue; Yongliang Wang; Lei Ma (Mycopathologia, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

3D-QSAR, HQSAR, molecular docking, and new compound design study of 1,3,6-trisubstituted 1,4-diazepan-7-ones as human KLK7 inhibitors - Le Fu; Yi Chen; Chun-mei Xu; Tao Wu; Hong-mei Guo; Zhi-hua Lin; Rui Wang; Mao Shu (Medicinal Chemistry Research, 2020)

Field survey of a catastrophic high-speed long-runout landslide in Jichang Town, Shuicheng County, Guizhou, China, on July 23, 2019 - Weihua Zhao; Rui Wang; Xiuwei Liu; Nengpan Ju; Mingli Xie (Landslides, 2020)

Characterization of a Rapeseed Anthocyanin-More Mutant with Enhanced Resistance to Sclerotinia sclerotiorum - Rui Liu; Li-Na Ding; Ming Li; Wei Cao; Yu-Kang Wang; Wei-Jie Wang; Yan-Kun Yu; Zheng Wang; Ke-Ming Zhu; Xiao-Li Tan (Journal of Plant Growth Regulation, 2020)

Diversity of the epiphytic bacterial communities associated with commercially cultivated healthy and diseased Saccharina japonica during the harvest season - Rui Zhang; Lirong Chang; Luyang Xiao; Xiaoyang Zhang; Qi Han; Nan Li; Suhelen Egan; Gaoge Wang (Journal of Applied Phycology, 2020)

Assessment of genetic diversity in Camellia oleifera Abel. accessions using inter-simple sequence repeat (ISSR) and start codon targeted (SCoT) polymorphic markers - Pu Xiao; Huhu Liu; Dongping Wang; Wenyan Tang; Hui Yang; Chong Wang; Zhilong He; Rui Wang; Xiangnan Wang; Xiangyang Lu; Yongzhong Chen; Yun Tian (Genetic Resources and Crop Evolution, 2020)

Rapid and efficient removal of naproxen from water by CuFe2O4 with peroxymonosulfate - Rui Bai; Yong Xiao; Weifu Yan; Siqi Wang; Rui Ding; Fan Yang; Junpeng Li; Xiaoquan Lu; Feng Zhao (Environmental Science and Pollution Research, 2020)

Late Early-Cretaceous Magma Mixing in the Langqi Island, Fujian Province, China: Evidences from Petrology, Geochemistry and Zircon Geochronology - Liangliang Huang; Liyuan Wang; Hong-Rui Fan; Musen Lin; Wenhui Zhang (Journal of Earth Science, 2020)

Quantitative assessment of the influence of terrace and check dam construction on watershed topography - Guowei Pang; Qinke Yang; Chunmei Wang; Rui Li; Lu Zhang (Frontiers of Earth Science, 2020)

Efficient mixed-domain pure P-wave equations for 2D and 3D tilted transversely isotropic media - Bowen Li; Deli Wang; Jinju Zhou; Qianxiang Zhang; Rui Wang (Acta Geophysica, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Causes and Treatment Measures of Submarine Pipeline Free-Spanning - Bo Zhang; Rui Gong; Tao Wang; Zhuo Wang (Journal of Marine Science and Engineering, 2020)
Submarine pipelines, as arteries for offshore oil and gas transportation, play a particularly important role in the exploitation of offshore oil and gas resources. Since the world’s first submarine pipelines were laid in the Gulf of Mexico, numerous failures have been caused by pipeline free-spanning. This paper provides a review of the causes and treatment measures for the free span of submarine pipeline. Various factors cause the free span of submarine pipelines, including wave flow scouring, fluctuations in seabed topography, residual stress or thermal stress of pipelines, and human activities. The scour of the wave current is the main factor affecting free span; the research on sediment starting and equilibrium depth during scour is reviewed in-depth. For the span treatment of submarine pipelines, the main measures available at present include the re-digging trench burying, structural support, covering bionic water plants, and choke plate self-burying. For each, the principle, advantages, disadvantages, and research are discussed. This review provides a convenient resource for understanding the causes of submarine free-spanning pipelines and choosing suitable treatment measures.

Two new eremophilane Sesquiterpenoides from Ligularia dictyoneura - Wenjing Wang; Rui Zhan; Yegao Chen (Natural Product Research, 2020)

Effect of decreasing soil frozen depth on vegetation growth in the source region of the Yellow River for 1982–2015 - Rui Wang; Zhibao Dong; Zhengchao Zhou (Theoretical and Applied Climatology, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Two-Dimensional Discrepancies in Fracture Geometric Factors and Connectivity Between Field-Collected and Stochastically Modeled DFNs: A Case Study of Sluice Foundation Rock Mass in Datengxia, China - Wen Zhang; Rui Fu; Chun Tan; Zhifa Ma; Ying Zhang; Shengyuan Song; Peihua Xu; Shuonan Wang; Yunpeng Zhao (Rock Mechanics and Rock Engineering, 2020)

A Moso bamboo gene VQ28 confers salt tolerance to transgenic Arabidopsis plants - Xinran Cheng; Yujiao Wang; Rui Xiong; Yameng Gao; Hanwei Yan; Yan Xiang (Planta, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

New cytotoxic bufadienolides from the roots and rhizomes of Helleborus thibetanus Franch - Yuze Li; Huawei Zhang; Xiaofei Liang; Bei Song; Xudong Zheng; Rui Wang; Li Liu; Xiaomei Song; Jianli Liu (Natural Product Research, 2020)

A salient oceanic driver for the interannual variability of wintertime haze days over the Pearl River Delta region, China - Yue Chang; Jing Wang; Zhiwei Zhu; Hua Deng; Jinhai He; Rui Lu (Theoretical and Applied Climatology, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

Development of 19 novel microsatellite markers of lily-of-the-valley (Convallaria, Asparagaceae) from transcriptome sequencing - Qi-Xiang Lu; Jing Gao; Jun-Jie Wu; Xuan Zhou; Xue Wu; Meng-Di Li; Yu-Kun Wei; Rui-Hong Wang; Zhe-Chen Qi; Pan Li (Molecular Biology Reports, 2020)

Minor topography governing erosional distribution of SOC and temperature sensitivity of CO2 emissions: comparisons between concave and convex toposequence - Yao He; Yaxian Hu; Xin Gao; Rui Wang; Shengli Guo; Xianwen Li (Journal of Soils and Sediments, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Improve uridine production by modifying related metabolic pathways in Bacillus subtilis - Xueting Zhang; Chen Wang; Lu Liu; Rui Ban (Biotechnology Letters, 2020)

Disruption of the lactate dehydrogenase and acetate kinase genes in Klebsiella pneumoniae HD79 to enhance 2,3-butanediol production, and related transcriptomics analysis - Jingping Ge; Jiawang Wang; Guangbin Ye; Shanshan Sun; Rui Guo; Gang Song; Wenxiang Ping (Biotechnology Letters, 2020)

Numerical Study of Storm Surge Inundation in the Southwestern Hangzhou Bay Region During Typhoon Chan-Hom in 2015 - Kai Wang; Yijun Hou; Shuiqing Li; Mei Du; Rui Li (Journal of Ocean University of China, 2020)

MiR-430 Can Affect the Mesoderm Formation and Metamorphosis of Paralichthys olivaceus by Targeting lefty Gene - Rui Li; Zhenwei Wang; Minmin Sun; Meiting Peng; Jie Qi; Zhigang Wang (Journal of Ocean University of China, 2020)

Factors Controlling Deposition of Metallic Minerals in the Meng’entaolegai Ag-Pb-Zn Deposit, Inner Mongolia, China: Evidence from Fluid Inclusions, Isotope Systematics, and Thermodynamic Model - He Yang; Wanli Ma; Rui Wang; Xueli Ma; Keyong Wang (Journal of Earth Science, 2020)

Stable Isotope Evidence for Recent Global Warming Hiatus - Rui Wang; Zhongfang Liu (Journal of Earth Science, 2020)

Responses of Alpine Wetlands to Climate Changes on the Qinghai-Tibetan Plateau Based on Remote Sensing - Rui Wang; Min He; Zhenguo Niu (Chinese Geographical Science, 2020)

Characteristics, Sources, and Risks of Polycyclic Aromatic Hydrocarbons in Topsoil and Surface Water from the Liuxi River Basin, South China - Zhenglan Xie; Lei Gao; Zuobing Liang; Jianyao Chen; Shaoheng Li; Aiping Zhu; Yu Wu; Zhigang Yang; Rui Li; Zhuowei Wang (Archives of Environmental Contamination and Toxicology, 2020)

Genetic characterization and genome-wide association mapping for dwarf bunt resistance in bread wheat accessions from the USDA National Small Grains Collection - Tyler Gordon; Rui Wang; David Hole; Harold Bockelman; J. Michael Bonman; Jianli Chen (Theoretical and Applied Genetics, 2020)
Key message Dwarf bunt-resistant bread wheat accessions and SNP markers associated with DB resistance identified in this study are valuable resources for characterization and deployment of DB resistance in bread wheat. Abstract Dwarf bunt (DB), caused by Tilletia controversa J.G. Kühn, can significantly reduce grain yield and quality on autumn-sown wheat in regions with prolonged snow cover. DB can be managed with the use of resistant cultivars. The objectives of the present study were to characterize DB resistance in a large set of bread wheat accessions from the National Small Grains Collection and use a genome-wide association study approach to identify genetic loci associated with DB resistance. A total of 292 accessions were selected using historical DB resistance data recorded across many trials and years in the Germplasm Resources Information Network (GRIN) and re-tested for DB resistance in replicated field nurseries in Logan, UT, in 2017, 2018, and 2019. Ninety-eight accessions were resistant with DB normalized incidence ≤ 10%, and twenty-eight of these were highly resistant with DB normalized incidence ≤ 1% in both GRIN and the field nurseries. Based on the presence of marker haplotypes of the four published dwarf bunt QTL on 6DS, 6DL, 7AL, and 7DS, highly resistant accessions identified in this study may provide novel resistance and should be further evaluated. This study validated one previously identified QTL on 6DS and identified an additional locus on 6DS. These loci explained 9–15% of the observed phenotypic variation. The resistant accessions and molecular markers identified in the present study may provide valuable resources for characterization and deployment of DB resistance in bread wheat.

LIN9 confers paclitaxel resistance in triple negative breast cancer cells by upregulating CCSAP - Hongna Lai; Rui Wang; Shunying Li; Qianfeng Shi; Zijie Cai; Yudong Li; Yujie Liu (Science China Life Sciences, 2020)

miR477 targets the phenylalanine ammonia-lyase gene and enhances the susceptibility of the tea plant (Camellia sinensis) to disease during Pseudopestalotiopsis species infection - Shuangshuang Wang; Shengrui Liu; Lu Liu; Rui Li; Rui Guo; Xiaobo Xia; Chaoling Wei (Planta, 2020)

Molecular cloning and functional characterization of the CEP RECEPTOR 1 gene MdCEPR1 of Apple (Malus × domestica) - Rui Li; Jian-Ping An; Chun-Xiang You; Xiao-Fei Wang; Yu-Jin Hao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

Heritability of resistance-related gene expression traits and their correlation with body size of clam Meretrix petechialis - Fengjuan Jiang; Xin Yue; Shujing Zhang; Jiajia Yu; Rui Wang; Baozhong Liu; Hongxia Wang (Journal of Oceanology and Limnology, 2020)

An improved finite element model for the hydraulic analysis of drip irrigation subunits considering local emitter head loss - Jian Wang; Rui Chen (Irrigation Science, 2020)

Comparative study on adsorption and immobilization of Cd(II) by rape component biomass - Chao Hu; Hongqing Hu; Yafang Tang; Yujun Dai; Zefeng Wang; Rui Yan (Environmental Science and Pollution Research, 2020)

Structural path analysis of China’s coal consumption using input–output frameworks - Ligao Yang; Lulu Li; Kunfu Zhu; Rui Xie; Zhenguo Wang (Environmental Science and Pollution Research, 2020)

Effects of structural planes on rockburst position with respect to tunnel cross-sections: a case study involving a railway tunnel in China - Lei Hu; Xia-Ting Feng; Ya-Xun Xiao; Rui Wang; Guang-Liang Feng; Zhi-Bin Yao; Wen-Jing Niu; Wei Zhang (Bulletin of Engineering Geology and the Environment, 2020)

Using environmental DNA to detect Hypophthalmichthys molitrix during the spawning period in the Yangtze River - Rui Ruan; Dengqiang Wang; Huamei Yue; Chuangju Li; Daqing Chen; Xinbin Duan (Conservation Genetics Resources, 2020)

The stability and pressure behavior characteristics of a special L-type face end formed by low-pressure mining technology without pre-driving roadway - Ya-jun Wang; Jun Yang; Man-chao He; Rui-feng Huang; Xi-chun Tian; Jian-ning Liu; Hao-jie Xue (Arabian Journal of Geosciences, 2020)

Separating and imaging diffractions in dip domain on the basis of slope analysis - Xue Kong; De-Ying Wang; Zhen-Chun Li; Rui-Xiang Zhang; Qiu-Yuan Hu (Applied Geophysics, 2020)

Detection performance of azimuthal electromagnetic logging while drilling tool in anisotropic media - Zhen-Guan Wu; Lei Wang; Yi-Ren Fan; Shao-Gui Deng; Rui Huang; Tao Xing (Applied Geophysics, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Simulation of T-bar penetration in soft clay with adhesive contact - Teng Wang; Rui Wu; Wenlong Liu; Xingxian Bao (Marine Georesources & Geotechnology, 2020)

Inhibition of methicillin-resistant Staphylococcus aureus (MRSA) biofilm by cationic poly (D, L-lactide-co-glycolide) nanoparticles - Yang Qiu; Yuqi Wu; Boyao Lu; Guanyin Zhu; Tao Gong; Rui Wang; Qiang Peng; Yuqing Li (Biofouling, 2020)

High risk of activation of latent tuberculosis infection in rheumatic disease patients - Wei Long; Fen Cai; Xinyi Wang; Nan Zheng; Rui Wu (Infectious Diseases, 2020)

Age- and region-related response of radial growth to climate warming and a warming hiatus - Lingnan Zhang; Rui Wang; Xianfeng Liu; Yilin Ran; Shu Shang; Xiaohong Liu (Trees, 2020)

Impact of Sugarcane–Legume Intercropping on Diazotrophic Microbiome - Manoj Kumar Solanki; Fei-Yong Wang; Chang-Ning Li; Zhen Wang; Tao-Ju Lan; Rajesh Kumar Singh; Pratiksha Singh; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2020)

Decreasing intraocular pressure significantly improves retinal vessel density, cytoarchitecture and visual function in rodent oxygen induced retinopathy - Rui Du; Xu Wang; Ke Shen; Shigang He (Science China Life Sciences, 2020)

Differential anthocyanin accumulation in radish taproot: importance of RsMYB1 gene structure - Biao Lai; Yuanyi Cheng; Hong Liu; Qiuxia Wang; Qi Wang; Chunlan Wang; Rui Su; Fabo Chen; Huicong Wang; Lina Du (Plant Cell Reports, 2020)

Remobilization of metasomatized mantle lithosphere: a new model for the Jiaodong gold province, eastern China - Jun Deng; Qingfei Wang; M Santosh; Xuefei Liu; Yayun Liang; Liqiang Yang; Rui Zhao; Lin Yang (Mineralium Deposita, 2020)

Random forest–based classsification and analysis of hemiplegia gait using low-cost depth cameras - Guoliang Luo; Yean Zhu; Rui Wang; Yang Tong; Wei Lu; Haolun Wang (Medical & Biological Engineering & Computing, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Sol-gel hydrothermal synthesis of nano crystalline silicotitanate and its strontium and cesium adsorption - Rong Wang; Zhenggang Luo; Qiuxia Tan; Rui Wang; Shuyuan Chen; Jiancheng Shu; Mengjun Chen; Zhengxue Xiao (Environmental Science and Pollution Research, 2020)

Application of loop-mediated isothermal amplification combined with lateral flow dipstick to rapid and sensitive detection of Alexandrium catenella - Liang Wang; Guofu Chen; Chunyun Zhang; Yuanyuan Wang; Rui Sun (Environmental Science and Pollution Research, 2020)

Mercury exposure in sedentary and migratory Charadrius plovers distributed widely across China - Tongping Su; Xin Lin; Qin Huang; Demeng Jiang; Chi Zhang; Xuecong Zhang; Caroline Dingle; Eben Goodale; Pinjia Que; Rui Wang; Yang Liu (Environmental Science and Pollution Research, 2020)

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

Quantitative proteomic analysis reveals that the Rap1/MAPK/ERK pathway is inhibited through selenomethionine strengthening antioxidant activity - Zhe Liu; Feng Zhang; Lina Cui; Jihong Wang; Ping Lu; Rui Zhao; Hua Zhang; Jianfa Wang; Chunqiu Li; Rui Wu (BioMetals, 2020)

Resonance characteristics of onshore wind turbine tower structure considering the impedance of piled foundations - Lujiong Wang; Rui Zhong; Lin Liu (Arabian Journal of Geosciences, 2020)

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

Competitive interactions between two allelopathic algal species: Heterosigma akashiwo and Phaeodactylum tricornutum - Rui Wang; Qiaona Xue; Jiangtao Wang; Liju Tan (Marine Biology Research, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

A Three-Dimensional Failure Criterion for Hard Rocks Under True Triaxial Compression - Xia-Ting Feng; Rui Kong; Chengxiang Yang; Xiwei Zhang; Zhaofeng Wang; Qiang Han; Gang Wang (Rock Mechanics and Rock Engineering, 2020)

Droplet-vitrification for shoot tip cryopreservation of shallot (Allium cepa var. aggregatum): effects of PVS3 and PVS2 on shoot regrowth - Min-Rui Wang; Zhibo Zhang; Jiří Zámečník; Alois Bilavčík; Dag-Ragnar Blystad; Sissel Haugslien; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Characterization and fine mapping of Arabidopsis RLL3, a locus required for DNA demethylation pathway - Wei Miao; Jie Dai; Yumei La; Chong Lu; Jianzhen Zhang; Xinyue Hong; Shaoxia Zhou; Qianqian Wang; Xiangyu Wang; Qi Rui; Feng Tan; Honggui La (Molecular Genetics and Genomics, 2020)

Stimulation of heterotrophic nitrification and N2O production, inhibition of autotrophic nitrification in soil by adding readily degradable carbon - Ting Lan; Rui Liu; Helen Suter; Ouping Deng; Xuesong Gao; Ling Luo; Shu Yuan; Changquan Wang; Deli Chen (Journal of Soils and Sediments, 2020)

Uptake and accumulation of pentachloronitrobenzene in pak choi and the human health risk - Ming Li; Guanghui Xu; Rui Yu; Yang Wang; Yong Yu (Environmental Geochemistry and Health, 2020)

Evaluation on activation energy of deposited clay based on thermo-gravimetric analysis (TGA) and four kinetics models - Rui-xin Yan; Jian-bing Peng; Yan-jun Shen; Yu-liang Zhang; Lin-jun Gu; Shao-kai Wang (Bulletin of Engineering Geology and the Environment, 2020)

Selenium Mitigates Cadmium-Induced Adverse Effects on Trace Elements and Amino Acids Profiles in Chicken Pectoral Muscles - Kui-Chao Qu; Hui-Qin Li; Kou-Kou Tang; Zhen-Yong Wang; Rui-Feng Fan (Biological Trace Element Research, 2020)

CD271 promotes STZ-induced diabetic wound healing and regulates epidermal stem cell survival in the presence of the pTrkA receptor - Min Zhang; Rui Zhang; Xiaohong Li; Yongqian Cao; Kaifeng Huang; Jun Ding; Mengyao Liu; Zhang Feng; Siyuan Yin; Jiaxu Ma; Huayu Zhang; Yibing Wang (Cell and Tissue Research, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

A Bayesian approach to seismic inversion based on GASA algorithm - Rui-qing Hu; Yan-chun Wang; Yang Gao; Shao-he Cao; Zhan-wei Yue; Qi Wang (Arabian Journal of Geosciences, 2020)

Preparation and In vitro Evaluation of FDM 3D-Printed Ellipsoid-Shaped Gastric Floating Tablets with Low Infill Percentages - Di Chen; Xiang-Yu Xu; Rui Li; Gen-Ao Zang; Yue Zhang; Ming-Rui Wang; Meng-Fei Xiong; Jia-Rui Xu; Ting Wang; Hui Fu; Qin Hu; Bin Wu; et al. (AAPS PharmSciTech, 2020)

Analysis of spatiotemporal variability in temperature extremes in the Yellow and Yangtze River basins during 1961–2014 based on high‐density gauge observations - Zigeng Niu; Lunche Wang; Lulu Fang; Jiarui Li; Rui Yao (International Journal of Climatology, 2020)
The Yellow and Yangtze River basins are the most important basins in China due to their environment and natural and socioeconomic conditions, and they are highly sensitive to extreme climate events. In this study, we used daily maximum and minimum temperature data gathered from 892 meteorological stations to analyse the spatiotemporal variations in temperature extremes in the Yellow and Yangtze River basins during 1961–2014 and identified correlations with the geographic location and atmospheric circulation patterns. The results indicated that annual mean maximum and minimum temperatures ( TX m and TN m ), most warm extremes and some cold extremes (minimum of the minimum temperature and maximum temperature, TN n and TX n ) generally showed low values in the northwestern region of the Yellow and Yangtze basins, while the diurnal temperature range (DTR) and some cold extremes (ice days, ID 0 and frost days, FD 0 ) were generally higher in the northwest of the two basins. TX m , TN m , all warm extremes and some cold extremes ( TN n and TX n ) showed significant increasing trends in both basins. The increase in the extreme temperature was between 0.17–0.38°C/decade in the Yellow basin, while the interval was 0.15–0.38°C/decade in the Yangtze basin. DTR decreased by −0.07 days/decade in the former and −0.05 days/decade in the latter. Furthermore, warm event days increased by 1.38–3.52 and 1.42–2.65 days/decade in the Yellow and Yangtze basins, respectively. At the same time, the cold event days decreased by −1.90 to −3.47 and −0.20 to −2.70 days/decade in the respective basins. In terms of the spatial patterns, most stations that displayed significant trends were located over the Loess Plateau in the Yellow River basins; Sichuan basin and the lower reaches of the Yangtze River basins. Moreover, almost all of the temperature extremes exhibited the largest trends in spring and winter in the two basins. Most temperature extremes showed strong correlations with longitude and altitude and the Atlantic Multidecadal Oscillation (AMO) displayed significant correlations with almost all of the temperature extremes, except DTR, TN n and TX n ; the East Atlantic/Western Russia (EA/WR) was also related to many temperature extremes. Finally, most temperature observations showed abrupt changes in the 1990s, and the timing in the Yangtze River basin was generally later than that in the Yellow River basin.